Nonequilibrium ecology - Rohde, Klaus, 1932- (Ecology, biodiversity, and conservation., 2005)
"This book is unique in focusing on nonequilibrium aspects of ecology, providing evidence for nonequilibrium and equilibrium in populations (and metapopulations), in extant communities and in ecological systems over evolutionary time, including nonequilibrium due to recent and present mass extinctions. The assumption that competition is of overriding importance is central to equilibrium ecology, and much space is devoted to its discussion. As communities of some taxa appear to be shaped more by competition than others, an attempt is made to find an explanation for these differences."--Jacket